Religiusitas Nelayan Pesisir Pantai Selatan dalam Bingkai Heterogenitas Sosial Masyarakat - Baedowi, Muhamad; Kurnia Putri , Widya Ayu; Sumantri, Rifki Ahda; Chamadi, Muhamad Riza; Musmuallim, Musmuallim (Universitas Muhammadiyah Yogyakarta, 2024)
Fishing communities live, grow and develop in coastal areas or coastal areas. In the social construction of communities in coastal areas, fishing communities are part of this social construction, although it is realized that not all villages in coastal areas have residents who make their living as fishermen. This research aims to determine the level of religiosity of fishermen on the southern coast of Tanggulangin Village, Kec. Klirong District. Kebumen using theory according to Gibson (2020), namely by using indicators of belief, religious practice, experience, religious knowledge and consequences. This type of research is field research where data is taken through interviews, observations, documents so that later conclusions can be drawn in this research. The results of this research are that the fishing community in Tanggulangin Village, Kec. Klirong District. Kebumen is still included in the fifth category of indicators, namely there is still belief in God, there is still religious practice, there is still fear of committing sins (experience), there is still a need for deeper religious knowledge and Consequence Indicators by attending religious activities.